2019
DOI: 10.1029/2018ja026229
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Thermospheric Density Between GUVI Dayside Limb Data and CHAMP Satellite Observations: Based on Empirical Model

Abstract: The Global Ultraviolet Imager (GUVI) aboard the Thermosphere-Ionosphere-Mesosphere Energetics and Dynamics (TIMED) satellite senses far ultraviolet airglow emissions in the thermosphere. The retrieved altitude profiles of thermospheric neutral density from GUVI daytime limb scans are significant for ionosphere-thermosphere study. Here, we use the profiles of the main neutral density to derive the total mass density during the period 2002-2007 under geomagnetic quiet conditions (ap < =12). We attempt to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 48 publications
(82 reference statements)
1
27
0
Order By: Relevance
“…Emmert et al () presented the first validation of mass density from GUVI limb retrievals by comparing with that from satellite orbit data. Yu et al () demonstrated that GUVI daytime observations are in good conformity with the Challenging Minisatellite Payload (CHAMP) satellite observations. Those all represent the validation of GUVI limb neutral density profiles.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Emmert et al () presented the first validation of mass density from GUVI limb retrievals by comparing with that from satellite orbit data. Yu et al () demonstrated that GUVI daytime observations are in good conformity with the Challenging Minisatellite Payload (CHAMP) satellite observations. Those all represent the validation of GUVI limb neutral density profiles.…”
Section: Introductionmentioning
confidence: 71%
“…The number of observations are sufficient except some bins in high latitudes, in twilight (<6 and >18 LT), and at high noon (11)(12)(13). The issue of GUVI data volume has been analyzed in detail in Yu et al, (2019). The coefficients of obtained from the Eq.…”
Section: Appendix B: Guvi Data Volume In Fixed Binsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the above decomposed EOFs are further fitted to the dayside total mass density from the GUVI EM model (ρ E ), ρE)(,,,,doyφλLTnormaldh=normalk=1NAkE)(,,doyφλ·EkM)(,LTnormaldh, where N is the truncation order of the EOFs and is set to 5, which is explained above. LT d represent the dayside time, 7–11 LT and 14–18 LT, namelythe time period that has adequate GUVI data volume described in the previous work (Yu et al, ). ρ E is the corresponding dayside results of GUVI EM density.…”
Section: Methodsmentioning
confidence: 99%
“…However, the uneven coverage of GUVI data volume and observation gaps especially in nightside limit the application of GUVI limb observations for the thermospheric structures and their variability studies (Yu et al, ). Therefore, making better use of the sparse GUVI limb altitude profiles are the developmental imperative of thermosphere study.…”
Section: Introductionmentioning
confidence: 99%